Prinsip Induksi Matematika dalam Pengambilan Keputusan Organisasi - Atmaja, I Made Dharma (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2024)
The principle of mathematical induction can be an effective tool in organizational decision making. Although these principles have the potential to increase efficiency, reduce uncertainty, and increase accuracy in organizational decision making, their application is limited and has not been fully exploited. Studies need to be conducted to bridge this gap by strengthening the understanding and application of the principles of mathematical induction in the context of organizational decision making. By considering the gaps that occur, it is necessary to conduct research on "The Principle of Mathematical Induction in Organizational Decision Making". This research provides an overview of how the principles of mathematical induction can bridge this gap and improve the quality of decision making in an organizational context. The research method used in this research is a qualitative approach and literature study which involves analysis of relevant literature related to the principles of mathematical induction in the context of organizational decision making. The conclusions from this research are: 1) Applying the principles of mathematical induction in organizational decision making can strengthen efficiency, reduce uncertainty, and increase accuracy in decision making; 2) In applying the principles of mathematical induction in organizational decision making, there are obstacles and challenges that need to be overcome; and 3) Utilizing the principles of mathematical induction involves the use of structured methods, in-depth analysis, and a more objective approach.